2014
DOI: 10.1159/000360619
|View full text |Cite
|
Sign up to set email alerts
|

Can Anti-AQP4 Antibody Damage the Blood-Brain Barrier?

Abstract: Background: Aquaporin 4 (AQP4) is a water-channel protein predominantly expressed in astrocyte end feet that make up the blood-brain barrier (BBB). Recently, anti-AQP4 antibody has been identified as a specific biomarker of neuromyelitis optica (NMO). However, whether anti-AQP4 antibodies damage the BBB is unclear. Methods: We evaluated BBB damage in patients with NMO and multiple sclerosis by measuring albumin leakage (AL) and studied its correlation with anti-AQP4 antibody. Results: No obvious difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Secondly, we find that BBB permeability is positively correlated to serum anti-AQP4-IgG titer. Whether merely serum anti-AQP4 IgG is sufficient to induce BBB disturbance is controversial ( 4 , 6 ). Asgari et al reported the BBB disturbance in mice after administering with anti-AQP4-IgG from NMO patients ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, we find that BBB permeability is positively correlated to serum anti-AQP4-IgG titer. Whether merely serum anti-AQP4 IgG is sufficient to induce BBB disturbance is controversial ( 4 , 6 ). Asgari et al reported the BBB disturbance in mice after administering with anti-AQP4-IgG from NMO patients ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Asgari et al reported the BBB disturbance in mice after administering with anti-AQP4-IgG from NMO patients ( 4 ). However, Akaza et al found that anti-AQP4-IgG was not associated with BBB damage ( 6 ). Our results further support the first perspective, and establish the quantitative link between BBB permeability and serum anti-AQP4-IgG titer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical data consisted of IVMP efficacy, 10 clinical findings and four CSF parameters. The clinical findings comprised of: (i) age at relapse; (ii) sex; (iii) EDSS (at baseline before relapse, before IVMP initiation during relapse, at 7 days after IVMP initiation, at discharge and differences in EDSS, such as [i] increase in EDSS between at baseline and before IVMP: ΔEDSS [baseline – pre‐IVMP]; [ii] decrease in EDSS between before IVMP and at 7 days after IVMP: ΔEDSS [pre‐IVMP – post‐IVMP]; [iii] those between 7 days after IVMP and at discharge: ΔEDSS [post‐IVMP – discharge]; and [iv] those between before IVMP and at discharge: ΔEDSS [pre‐IVMP – discharge]); (iv) lesion site (spinal cord or brain); (v) gadolinium (Gd) enhanced lesion on MRI; (vi) number of relapses (the first attack was defined as one); (vii) complication with other autoantibodies (coexistence or not); (viii) immunosuppressant drugs (oral prednisolone [PSL] dose before relapse, mg/day; frequency of calcineurin inhibitor [CNI] use, %); (ix) total dose of IVMP used at the relapse phase (g/3−6 days); and (x) time‐period from exacerbation to IVMP initiation (days) . The CSF parameters consisted of: (i) CSF‐cells (count/μL); (ii) CSF‐lactate dehydrogenase (CSF‐LDH; IU/L); (iii) CSF/serum quotient of albumin (Q‐ALB; Q‐ALB × 10 3 ), which is a marker of the permeability of the blood–brain barrier (BBB); and (iv) CSF/serum quotient of immunoglobulin G (Q‐IgG; Q‐IgG × 10 3 ) .…”
Section: Methodsmentioning
confidence: 99%